Increasing Diversity at the Highest Levels of Nursing: Perspectives of a Doctor of Nursing Practice Graduate - Monica Jaramillo (OPI Napoli, 2023)
Introduction: There is a need to increase diversity at the highest levels of education in nursing to ensure competent transcultural services for the growing multicultural population worldwide. The Doctor of Nursing Practice (DNP) is a terminal degree that significantly impacts change advocacy. This commentary includes the perspectives of an immigrant nurse in her journey to completing a doctoral degree while contributing to diversity. Discussion: Diversity, Equity, Inclusion, and Accessibility (DEIA) positively impacts nursing and healthcare systems at many levels. It is imperative to advocate for equal services for all individuals while inspiring nurses and other healthcare professionals to further their careers by achieving advanced education degrees conducive to propelling health services forward. The author seeks to inspire nurses worldwide to continue their educational journey and encourage immigrants to believe they can do it despite their fears and hesitation.